Cascade One‐Pot Synthesis of Orange‐Red‐Fluorescent Polycyclic Cinnolino[2,3‐f]phenanthridin‐9‐ium Salts by Palladium(II)‐Catalyzed C−H Bond Activation of 2‐Azobiaryl Compounds and Alkenes - Jayakumar, Jayachandran; Vedarethinam, Guganchandar; Hsiao, Huan‐Chang; Sun, Shang‐You; Chuang, Shih‐Ching (Angewandte Chemie International Edition, 2020)
Quaternary ammonium salts were synthesized in moderate to good yields through double oxidative C−H bond activation on azobenzenes. The mechanism of the highly regioselective reaction of 2‐azobiaryls with alkenes to give orange‐red‐fluorescent cinnolino[2,3‐f]phenanthridin‐9‐ium salts and 15H‐cinnolino[2,3‐f]phenanthridin‐9‐ium‐10‐ide is proposed to involve ortho C−H olefination of the 2‐azobiaryl compound with the alkene, intramolecular aza‐Michael addition, concerted metalation–deprotonation (CMD), reductive elimination, and oxidation. Fired up: Orange‐red‐fluorescent cinnolino[2,3‐f]phenanthridin‐9‐ium salts were synthesized with high regioselectivity from 2‐azobiaryls and alkenes by palladium(II)‐catalyzed C−H activation under mild reaction conditions (see scheme). The prepared quaternary ammonium salts showed strong fluorescence emission maxima at 575–620 nm with broad bandwidths.